Knowledge and attitudes towards antibiotic resistance among health profession students in Indonesia - Syahniar, Rike; Farsida, Farsida; Kosasih, Audia Nizhma Nabila; Mardhia, Mardhia; Bekti, Heri Setiyo; Marpaung, Nurasi Lidya E.; Dharmawan, Ade; Indriyani, Indriyani; Husna, Ismalia; Amany, Hana Amirah (Intelektual Pustaka Media Utama, 2024)
Abuse and overuse of antibiotics cause the increasing prevalence of antibiotic resistance. Doctors, nurses, midwives, and pharmacy professionals play an essential role in providing information and education on the use of antibiotics to the public. This study aims to compare and identify the factors that influence the knowledge and attitudes of students’ medicine, midwifery, pharmacy, and nursing toward antimicrobial resistance. An online crosssectional survey involving 530 medical, midwifery, pharmacy, and nursing students who are currently in the clinical or professional study stage. The Mann–Whitney U test and the Kruskal–Wallis test was run to assess differences in the mean scores of knowledges and attitudes. Factors related to knowledge and attitudes regarding antibiotic resistance were analyzed using linear regression. Most (93%) students have a good level of knowledge and have a positive attitude 49.81%, neutral 43.78%, and negative 6.41%. There was a relationship between age (p=0.012), major (p=0.000), source of information (p=0.013), and knowledge and attitudes about antibiotics (p<0.05). We conclude that there are differences in knowledge and attitudes toward antibiotic resistance among clinical-stage students of medicine, midwifery, pharmacy, and nursing. We found that essential knowledge and attitudes should be revised regarding antibiotic resistance.